INFORMED CONSENT IN TEENAGE PREGNANCY: DOCTORS’ KNOWLEDGE, ATTITUDES AND PRACTICES AMONGST ANAESTHESIOLOGISTS AND OBSTETRICIANS IN SEVEN KWAZULU-NATAL HOSPITALS. - mapodile, maseoke; Cronjé, Larissa; Naidu , Sailuja (Student's Journal of Health Research Africa, 2024)
Background Teenage pregnancy is a global phenomenon. Informed consent practice regarding the sexual and reproductive rights of teenagers may be hampered by physicians’ lack of knowledge or attitude. The study aimed to assess the knowledge, attitudes, and practices of doctors in the process of obtaining informed consent from pregnant teenage patients in seven government-funded hospitals in KwaZulu-Natal. Methods A prospective, descriptive, observational study using a self-administered questionnaire was conducted amongst doctors working in Anaesthesia and Obstetrics and Gynecology, from 15 October 2021 to 30 November 2021. Results A total of 169 doctors participated in the study, 62.7% from anesthesia and 37.3% from Obstetrics and Gynaecology. Most doctors lacked knowledge regarding the Children's Act No. 38 of 2005 and the Choice on Termination of Pregnancy Act No. 92 of 1996. Approximately 18% of doctors reported obtaining consent for any medical intervention in teenage pregnant patients solely from their parent(s) or guardian, irrespective of the patient’s mental or legal capacity. A fifth (19.5%) of doctors reported that interns were responsible for obtaining informed consent without supervision. Most doctors disclose legally required information in the language the pregnant teenage patient understands, with the assistance of a translator if required. Some doctors revealed paternalistic views regarding teen pregnant patients’ right to choose medical intervention available. Conclusion The study found that although doctors met the general legal requirements for informed consent, in most cases, they lacked core knowledge of the relevant acts and laws for sexually active teenagers, thus affecting the validity of the informed consent process. Recommendation This could be improved by focusing on filling this knowledge gap at both an undergraduate and postgraduate level as well as a review of the laws/acts that pertain to this population group.